A Comparison of Ligase Chain Reaction to Polymerase Chain Reaction in the Detection of Chlamydia trachomatis Endocervical Infections. Issue 2 (1998) - Davis, J. D.; Riley, P. K.; Peters, C. W.; Rand, K. H.
Abstract : Objective: To compare the reliability of ligase chain reaction (LCR) to polymerase chain reaction (PCR) in detecting Chlamydia trachomatis endocervical infections. Methods: We conducted a prospective study of 486 patients at risk for chlamydial infection of the endocervix. We obtained two endocervical specimens from each patient and used LCR and PCR to detect C. trachomatis . Discrepant results between the two techniques were resolved by repeat testing and by testing for the major outer membrane protein (MOMP) gene, if necessary. We determined the sensitivity, specificity, positive predictive value, and negative predictive value for each test, using concordant results or MOMP gene results as the "gold standard". Results: Of the 486 patients, 42 (8.6%) had evidence of C. trachomatis infection after resolution of discrepant results. Of the 42 true positive specimens, 41 were positive by initial LCR and 38 were positive by initial PCR. Of the 444 true negative specimens, none had a positive initial LCR result, while 2 had a positive initial PCR test. Therefore, compared to the gold standard, LCR had a sensitivity of 97.6% and specificity of 100%, while PCR had a sensitivity of 90% and a specificity of 99.5%. The positive and negative predictive values of LCR were 100% and 99.8%, respectively. PCR had a positive predictive value of 95% and a negative predictive value of 99.1%. The difference in sensitivity of LCR versus PCR was not statistically significant ( P = .125). Conclusion: LCR and PCR perform equally well in detecting C. trachomatis endocervical infections.